The Optimization of Pudding Formulation Using Noni (Morinda citrifolia L.) Seen from Antioxidant Content and Sensory Characteristics - Kristiawan Prasetyo Agung Nugroho; Monika Rahardjo; Apfia Jovitatera (Indonesian Journal of Agricultural Research, 2018)
Noni (Morinda citrifolia L.) is a fruit that known to be effective against many diseases. Its phenol and flavonoid contentacted as antioxidant, anticancer, antiinflamation and to fluent the blood vessel. Because of its content that rich in antioxidant, this research aim to utilized it as a food product. Pudding is one of food product that categorized as a dessert, which in the production does not require heat treatment, so the antioxidant can be maintained. The purpose of this experiment is to find the optimum formulation of Noni pudding seen from antioxidant content and sensory characteristics. The method of this research is total phenolic assay, total flavonoid assay and sensory evaluation from 50 random panelis age between 18-25 years old. The result showed that Noni fruit has total phenolic 0,13423 mg GAE/ml and the total flavonoid 0,11819 mg GAE/mL. The best formulation of pudding resulted from sensory evaluation was found with the addition 10% concentration of Noni extract 10%.